Questioning the Kantian Propositions: Explaining the Role of the United States as Democratic Peace Model in 21st Century - Kusumadewi, Hemalia (Global Focus, 2023)
Theorizing and manifesting peace through democracy has always been connected with Kantian propositions, making a country's attempt in realizing those two not to be separated  with Kantian theories also. The United States of America has been self-proclaimed as a ‘role model and promoter of democracy and peace’. To some extent this might be true, as its foreign policy key objective includes ‘promoting democracy and advocating human rights. However, the ‘role model’ also translates as an entity that needs to be ‘the best’, yet the 2021 Capital Riot reflects otherwise. This paper proposes the Kantian Peace Triangle as the framework to do the work, by breaking-down US’s policy and activities particularly in the Post-Cold War period. The paper uses qualitative approach and literature review method in the research. This paper argues that the US has not been able to reach the ‘ideal’ essence as a ‘role model of democracy and peace’ in the global order, and that this role has become mostly irrelevant in the 21st century world